If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(8p + -9) = -3(-12p + 8) Reorder the terms: 4(-9 + 8p) = -3(-12p + 8) (-9 * 4 + 8p * 4) = -3(-12p + 8) (-36 + 32p) = -3(-12p + 8) Reorder the terms: -36 + 32p = -3(8 + -12p) -36 + 32p = (8 * -3 + -12p * -3) -36 + 32p = (-24 + 36p) Solving -36 + 32p = -24 + 36p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-36p' to each side of the equation. -36 + 32p + -36p = -24 + 36p + -36p Combine like terms: 32p + -36p = -4p -36 + -4p = -24 + 36p + -36p Combine like terms: 36p + -36p = 0 -36 + -4p = -24 + 0 -36 + -4p = -24 Add '36' to each side of the equation. -36 + 36 + -4p = -24 + 36 Combine like terms: -36 + 36 = 0 0 + -4p = -24 + 36 -4p = -24 + 36 Combine like terms: -24 + 36 = 12 -4p = 12 Divide each side by '-4'. p = -3 Simplifying p = -3
| L=ml | | 2h+3-12h=9(-h+2) | | 12+5=7x-4 | | 9.7s+1.56=10.9s | | -11.2b+14.16=-14.54-14.7b | | 3(x+5)=2(x+12) | | 10.1d-12.57-16.6d=-4.9d+16.39 | | 250a=11000 | | 4.95+2.95(x-3)=21.83 | | 3x+1x+2=8x-4x+2 | | 4+3x-6=3x+-12-x | | -2x-2=-8x+10 | | 4x^2-1x= | | 4(2x+4)=10x+15-2x+1l | | Sinx+cosx=-1 | | Sinx+coax=-1 | | 12k=10.6k-17.92 | | 36+3q=-5 | | 2c-4=8 | | 19-3a=13+a | | 19.8f+15.79=-13.09-16.3f | | 19-5j=-5-3j | | 14+5z=6z | | 20+4n+20=14n-20 | | -8+7w=6w | | 3(3x+2)=2(3x-6) | | 10v-9=10-4v+9 | | 2/3x-6=6-2/3x | | 6-7c=-6-10c | | 6+y=-y | | m^4-6m^2+8m-3=0 | | 3x-2=26+4x |